Crafting the idea of multiculturality: The case of Wrocław, European Capital of Culture 2016 - Latusek, Dominika; Ratajczak, Magdalena (Scandinavian Journal of Public Administration, 2014)
This paper describes efforts in creating a new image of the city, on the example of Wrocław in Poland, using the case of its application of European Capital of Culture in 2016. We explore how the idea of multiculturality, that became a leading theme in Wrocław’s application for ECoC 2016, had been crafted in practice in the city that is, in fact, highly homogenous. We also analyze how history is being used in city branding and how it can be creatively used to managed the image of the city among the wide public. We conclude that Wrocław has been successful in creating the image of multiculturality and constitute an interesting example to study by both theoreticians and practitioners of public management.